8.1 Palynological studies in northeast Skye and Raasay (Scottish Historical and Archaeological Internet Reports, 2009)
Pollen, microscopic charcoal and radiocarbon studies at four sites on Skye and Raasay provide environmental contexts for the archaeological investigations of Scotlands's First Settlers around the Inner Sound. One coring site, from a loch in northern Trotternish, Skye, provides a regional summary of environmental change. Other sites closer to the rockshelter at An Corran, Trotternish, furnish more localised pictures of landscapes change, some of which may be associated with human intervention of Mesolithic age, Intertidal organic deposits from Raasay assist in reconstructing the early Holocene environment of the area.